Chemical safety as component of national security of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
In this article questions classifi cation of types of national security by spheres and activity areas, and as a result chemicalsafety as one of components of the general system of national security are considered.Key words: national security, chemical safety, law, state.